Mapping glaciers in Jotunheimen, South-Norway, during the "Little Ice Age" maximum - Baumann, S.; Winkler, S.; Andreassen, L. M. (The Cryosphere, 2009)
The maximum glacier extent during the "Little Ice Age" (mid 18th century AD) in Jotunheimen, southern Norway, was mapped using remote sensing techniques. Interpretation of existing glaciochronological studies, analysis of geomorphological maps, and own GPS-field measurements were applied for validation of the mapping. The length of glacier centrelines and other inventory data were determined using a Geographical Information System (GIS) and a Digital Elevation Model. "Little Ice Age" maximum extent for a total of 233 glaciers comprising an overall glacier area of about 290 km2 was mapped. Mean length of the centreline was calculated to 1.6 km. Until AD 2003, the area and length shrank by 35% and 34%, respectively, compared with the maximum "Little Ice Age" extent.